Krukväxter med mervärde till dagligvaruhandeln - Lihné-Carlsson, Marianne (2007)
The supermarkets are taking more and more market shares for potted plants the last years, and a greater part is bought without prior planning. Signals from several European countries, for example Denmark and UK, indicate that potted plants with added value have become more and more popular and the added value is based on present trends. The meaning of added value in this thesis is fancy pots, packaging, pins or arrangements. Potted plants with added value sold in supermarkets offer the consumer the advantage of getting a "ready product" quick and easy. The "ready product" can fulfil the need of a gift or the wish to decorate the home in a trendy way.